2004
DOI: 10.1016/s0911-6044(03)00057-5
|View full text |Cite
|
Sign up to set email alerts
|

Normal and pathological development of subject–verb agreement in speech production: a study on French children

Abstract: We report a study on the spoken production of subject -verb agreement in number by four age groups of normally developing children (between 5 and 8;5) and a group of 8 children with Specific Language Impairment (SLI; between 5;4 and 9;4), all French speaking. The production of verb agreement was experimentally elicited by asking children to complete sentence preambles containing a head noun and a potentially attracting 'local noun'. In contrast to previous studies that focused on attraction with local nouns wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 50 publications
7
34
0
Order By: Relevance
“…However, the plural effect we observe might be the result of an increase in 'default' singular number markings -an explanation that has been proposed in earlier studies, for instance by Hemforth and Konieczny (2003) or Franck et al (2004). This argument gains indirect support by our analysis of the distribution of repetition errors in our data, that is the number of errors where subjects reproduced the sentence preamble with one or more incorrect number markings on the noun.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, the plural effect we observe might be the result of an increase in 'default' singular number markings -an explanation that has been proposed in earlier studies, for instance by Hemforth and Konieczny (2003) or Franck et al (2004). This argument gains indirect support by our analysis of the distribution of repetition errors in our data, that is the number of errors where subjects reproduced the sentence preamble with one or more incorrect number markings on the noun.…”
Section: Discussionsupporting
confidence: 76%
“…1 A central claim of the explanation of the plural markedness effect by Eberhard (1997) is that number marking is based on a privative or unary feature specification, and that the featureless, 'unmarked', or default number is singular. A 'default' marking or singular bias has been suggested earlier by Hemforth and Konieczny (2003) as an explanation of their results from a written sentence completion study; also see Franck et al (2004) for a similar argument based on acquisition data. Eberhard (1997) presents evidence for the psychological reality of the unary specification of number by a grammatical feature, which is in line with common linguistic accounts of number marking.…”
Section: Agreement and Agreement Errorssupporting
confidence: 58%
“…Answering the question of whether syntactic production operates on the basis of syntactic factors requires us to adopt a theoretical framework that identifies these factors. Such research on agreement is relatively rare in experimental psycholinguistics, although some studies have started to point to the involvement of syntactic factors like the hierarchical structuring of the words (Bock & Cutting, 1992;Franck, Cronel-Ohayon, Chillier, Frauenfelder, Hamann and Rizzi, 2004;Franck, Vigliocco, & Nicol, 2002;Vigliocco & Nicol, 1998, see Section 2).…”
Section: Introductionmentioning
confidence: 99%
“…That is, languages normally admitting VS order often show flexibility in the realisation of agreement in these structures as compared to the corresponding SV configurations. It is important to note that this instability does not manifest itself as a chance realization of the marked (plural) or unmarked (singular) features: in all the cases of VS disagreement, a singular verb precedes a plural subject, never the other way around (for a discussion of the psycholinguistic relevance of the notion of markedness see for example Eberhard, 1997or Franck et al, 2004 for developmental arguments).…”
mentioning
confidence: 99%
“…Hence, feature copy is the locus of attraction effects in agreement. Experimental reports have shown that attraction depends on the position of the intervener in the hierarchical structure, not on its final, surface position (Bock & Cutting, 1992;Franck et al, 2004;Franck, Vigliocco, & Nicol, 2002;Hartsuiker, Antó n-Méndez, & van Zee, 2001;Vigliocco & Nicol, 1998). Finer structural variables identified in syntactic theory like the type of intervention relation (precedence vs. c-command) and the involvement of subject movement in the specifier of AgrS were also found to modulate attraction (Franck et al, 2006).…”
mentioning
confidence: 97%